A DFT Investigation of Structural, Electronic, Optical, and Mechanical Properties of Lead‐Free Novel InGeX3 (X = Cl, Br, and I) Perovskites for Potential Applications in Multijunctional Solar Cells - Md. Amran Sarker; Md. Mehedi Hasan; Sharmin Akhter Luna; Md. Imtiaz Hossain Chowdhury; Md. Rabbi Talukder; Md. Rasidul Islam; Sohail Ahmad (Energy Science & Engineering)
ABSTRACT Conducting an inquiry into the structural, mechanical, electrical, and optical aspects of Ge‐based InGeX3 (Cl, Br, and I) halide perovskites using the density functional theory approach is the main objective of this study. The investigation reveals that substituting the bigger halogen atoms (Br and I) with the smaller halide (Cl) enhances the structural stability of the compound. The largest values of lattice constant and unit cell volumes are found for the InGeI3 compound. Formation energy and born stability criteria are also calculated, which comprehend the compounds as chemically and mechanically stable. Elastic constants, mechanical properties, and anisotropy behavior of the compounds are also analyzed. The investigation explicitly demonstrates that InGeCl3 has superior ductility, machinability, and hardness as well. The anisotropy nature of all our studied compounds has also been discussed and visualized through three‐dimensional contour maps. Employing the GGA‐PBE and HSE06 functional, the band gap energy of each InGeX3 perovskite has been determined. In all our studied compounds, a direct band gap was observed at the high symmetrical point, R. The optical properties of the perovskites, including dielectric function, absorption coefficient, optical conductivity, reflectivity, refractive index, and extinction coefficient, have been analyzed. Overall, the results of the investigation conclude that InGeX3 perovskite compounds are the preferred material choice for effective performance in multijunctional solar cells and optoelectronic devices.